A voz de Calvino no Brasil colônia: uma avaliação da influência da teologia calvinista na Confissão de Fé da Guanabara - Oliveira, Marlon Antonio de (2018)
The present research aims to trace some contributions of the theology proposed by the protestant reformer John Calvin (1509-1564) in the formulation of the Confession of Faith of Guanabara (17/1/1558), since its authors were members of the Church of Geneva, where Calvin was a pastor. As Calvin's listeners and students, how much of the theology of the Reformer is imprinted in the letters and teachings of that Confession? This is the question to be answered, from that of an item-by-item examine of Confession compared with Calvinist writings. This research, for a better analysis, will focus only on the chapter of the Guanabara Confession that deals with the Sacraments, because it understands that this was the central point of the conflict with Villegagnon, and believing that only this portion will suffice, supported by other information, to prove the initial hypothesis. Then identify Protestant traits from this undertaking; and finally, to cite the possible contributions of the relation of Calvinist theology and the Confession of Faith of Guanabara, as a historical document, pointing out its implications for Protestant theological thinking in the current Brazilian scenario. The research concludes that there is reliable evidence of the influence of Calvin's thought and theology on the Guanabara Confession of Faith. Calvin was the pastoral and theological mentor of the Fluminense Confession. Calvin's voice is heard in the content of the Confession.